Desenvolvimento e avaliação de estratégias de rastreamento de doenças cardíacas na Atenção Primária à Saúde - Adriana Costa Diamantino Soares (2020)
Introduction: Access to public healthcare is limited in Brazilian underserved areas, and long waiting lists remain for echocardiography (echo). We aimed to develop a tool to optimize indications and shorten the waiting list for standard echo in primary care. Methods: Patients in waiting list for standard echo in Montes Claros, Brazil, were enrolled. For derivation, patients underwent a standardized clinical questionnaire, simplified 9-view echo screening by non-physicians with handheld devices (GE VSCAN), and standard echo (Vivid-Q) by experts. Two models were adjusted, one including clinical variables and other adding screen-detected major heart disease (HD). For validation, patients were risk-classified according to the clinical score. High-risk patients and a sample of low-risk underwent standard echo. Intermediate-risk patients first had screening echo, with a complete study if HD was suspected. Discrimination and calibration of the 2 models were assessed to predict HD in standard echo. Also for validation phase, patients were submitted to an atrial fibrillation screening (AFS) with a single derivation portable device (MyDiagnostick®). Results: In derivation (N=603), the clinical variables associated with HD were female gender, body mass index, Chagas disease, prior cardiac surgery, coronary disease, valve disease, hypertension, and heart failure, and this model was well calibrated with C-statistic of 0.781. Performance was improved with the addition of echo screening, with C-statistic of 0.871 after cross-validation. For validation (N = 1,526), 227 (14.9%) patients were classified as low risk, 1082 (70.9%) as intermediate risk, and 217 (14.2%) as high-risk by the clinical model. The final model with 2 categories had high sensitivity (99%) and negative predictive value (97%) for HD in standard echo. Model performance was good with C-statistic of 0.720. The AFS was positive in 6.4%: 12.6% high risk, 6.1% intermediate risk and 2.2% low risk. Older age was a risk factor (9.3% vs 4.8% in those more than and less than 65 years, p = 0.001). AFS positive was independently associated with heart disease in echo (OR = 3.9, 95% CI 2.1 to 7.2, p < 0.001). Conclusion: The addition of screening echo to clinical variables and the screening for AF significantly improves the performance of a score to predict major HD on primary care. Keywords: screening; primary health care; echocardiogram; public health; cardiopathies.